STRUCTURAL RETINAL ABNORMALITIES AS POTENITAL MARKERS FOR PSYCHOSIS SPECTRUM DISORDERS - Jerotić, Stefan; Marić, Nadja P (Medicinski podmladak, 2018)
Retinal nerve structures are the only part of central nervous system where neurons can be observed directly, in vivo. Great advances in retinal imaging have been made in the recent years. Some of this progress is due to use of optical coherence tomography scanners, common in ophthalmological clinical practice. Today, this method provides high precision in the visualization of retina, providing close to an “optical biopsy” of distinct retinal layers. Identification of biological markers that have diagnostic or therapeutic value in psychosis spectrum disorders is one of the most important tasks for current neurobiological research. Recently, new evidence for reduction of retinal structures such as retinal nerve fiber layer and ganglionic cell thickness in schizophrenia has emerged. In the present article, this and other evidence on retinal thinning in schizophrenia and related disorders is summarized and discussed. However, the current evidence is conflicting, owing to both the heterogeneity of the disorder, and the methodological differences of the described studies.